Does Working Culture Improve Employee Performance? The Mediation Role of Job Satisfaction Â - Suparjiman, Suparjiman; Satriawan, Budhi; Sondari, Tanty (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2024)
The role of work culture in improving employee performance is very important. In this case, every organization needs a good environment so that employees have satisfaction when doing their work. This research aims to look at the role of work culture on employee performance with job satisfaction as a mediator for MSME employees in the city of Bandung. This research used a descriptive verification approach, 118 employees were sampled and the technique used used a structural equation model with the help of Amos software version 21. Primary data from this research was obtained from a questionnaire. Meanwhile, secondary data was obtained through notes, publications, and literature. The research results show that organizational work culture has a positive and significant effect on job satisfaction and employee performance, and work culture has a positive effect on performance through job satisfaction. This research is proposed to determine aspects of work culture that are related to employee performance in MSMEs in the city of Bandung and also emphasize aspects of employee job satisfaction that have an impact on performance. It is hoped that the research results can expand the treasures of management literature, especially in the field of HR.